Alternatives and positions regarding the war between patriots and realists in the Andean space: The case of Captain Juan Antonio Acuña. 1819-1821 - Davio, Marisa (Hispania Nova, 2022)
From the study of a judicial case, related to a realist actor from Lima involved in process of independence and collaborator of general José de San Martin, we wonder about the strategies and alternatives of the realist -and revolutionaries- during the conflict that lasted more than twenty years in the Andean space, from the long process that began with the crisis of the Spanish monarchy in 1808 to the formal declarations of the Independence in the last royalist strongholds that still remained in these territories. We intend to observe the political landscape experienced by multiple contemporary actors who had to opt for the fight in favor of one or the other side in conflict, according to their convictions and political and economic pretensions, as result of uncertainty derived from the crisis monarchy of 1808 and the beginning of the revolutionary process in 1810 that would lead to the Independence of the countries in South America.